Pengaruh Kapabilitas Pemasaran, Digital Marketing Dalam Meningkatkan Kinerja Pemasaran UMKM Di Jawa Barat - Frans Sudirjo; Arief Yanto Rukmana; Hilarius Wandan; Muhammad Lukman Hakim (Universitas Nusa Putra, 2023)
This study aims to examine the influence of marketing capabilities and digital marketing on the marketing performance of micro, small, and medium enterprises (MSMEs) in West Java, Indonesia. Data were collected from 384 MSMEs using a structured questionnaire, and a structural equation modeling (SEM) was employed to test the research hypotheses. The results of the study indicate that marketing capabilities and digital marketing have a significant positive impact on the marketing performance of MSMEs. Furthermore, digital marketing was found to mediate the relationship between marketing capabilities and the marketing performance of MSMEs. These findings have important implications for MSMEs in West Java, as well as in other regions of Indonesia, and for policymakers and academics who are interested in supporting the growth and development of the MSME sector.